SUBTITUSI TEPUNG UBI JALAR DALAM PEMBUATAN BOLU GULUNG - Anton Ramadhan Ketra; Okta Wulandra (Agritepa, 2015)
Making rollscakewithsweetpotatofloursubstitution hasbeen done.Thisstudyaimedto analyzethelevelofpanelistpreferenceforcolor,flavorandtextureofsweetpotatorollscake.Thisstudyusedavariationofthetreatmentformulationsflourand sweetpotatowiththreetreatments,iecomparisonofsweetpotatoflour:wheatflour750grams:250grams ;500grams:500grams;250grams:750grams.Parametersmeasuredwerepanelistspreferencelevelofthecolor,flavorandtexture.Theresultsshowedthatthesweetpotatoflourrollsinlikemostconsumersistheformulationofsweetpotatoflour500gramsand 500gramsofwheatflour. Keywords:rollscake,flour,sweetpotatoflour